2023
DOI: 10.1038/s41467-023-44037-w
|View full text |Cite|
|
Sign up to set email alerts
|

Carbonate chemistry and carbon sequestration driven by inorganic carbon outwelling from mangroves and saltmarshes

Gloria M. S. Reithmaier,
Alex Cabral,
Anirban Akhand
et al.

Abstract: Mangroves and saltmarshes are biogeochemical hotspots storing carbon in sediments and in the ocean following lateral carbon export (outwelling). Coastal seawater pH is modified by both uptake of anthropogenic carbon dioxide and natural biogeochemical processes, e.g., wetland inputs. Here, we investigate how mangroves and saltmarshes influence coastal carbonate chemistry and quantify the contribution of alkalinity and dissolved inorganic carbon (DIC) outwelling to blue carbon budgets. Observations from 45 mangr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Therefore, the storage of soil organic carbon (SOC) assumes critical importance in regulating the carbon cycle and ameliorating climate change. Salt marsh wetlands, one of the most vital blue carbon systems, store a large amount of soil organic carbon because of the high net primary productivity and low soil organic matter decomposition rate [6,7]. According to research, the carbon burial rate in salt marshes is 30-50 times that of terrestrial forests, and 50%-90% of the carbon is stored in the soil [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the storage of soil organic carbon (SOC) assumes critical importance in regulating the carbon cycle and ameliorating climate change. Salt marsh wetlands, one of the most vital blue carbon systems, store a large amount of soil organic carbon because of the high net primary productivity and low soil organic matter decomposition rate [6,7]. According to research, the carbon burial rate in salt marshes is 30-50 times that of terrestrial forests, and 50%-90% of the carbon is stored in the soil [8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research is focused on the environmental and economic effects of ocean carbon sinks. Scholars found that shellfish, mangroves, and plankton are strong carbon sinks with ecological and environmental functions of increasing carbon sinks and reducing carbon sources (World Ocean Review, 2010;Reithmaier et al, 2023). They also researched nearshore aquaculture's carbon sequestration process and mechanism (Camp et al, 2016).…”
mentioning
confidence: 99%